The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/0022-3727/45/3/035302
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between space charge accumulation in polyethylene and its fluorinated surface layer characteristics

Abstract: Polyethylene (PE) samples were surface fluorinated by the F2/N2 mixture for 30, 60, 120 or 240 min to investigate the influence of the fluorinated layer characteristics on space charge accumulation. After polarization at 50 kV mm−1 dc electrical field and 40 °C for 240 min, the charge amounts of the samples fluorinated for the different times, normalized to the charge amount of the original sample, are 1.17, 0.51, 0.49 and 0.22, respectively, showing significant suppression of the charge accumulation by the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…[11][12][13] By controlling treatment factors during the direct fluorination process, a surface layer containing C-F bonds with preferable surface properties can be obtained. 14,15 In An's research, by controlling direct fluorination time and temperature, different surface conductivities are obtained in epoxy resins. [16][17][18] The dc surface flashover voltage of the epoxy resin is also found improved after direct fluorination.…”
Section: -2mentioning
confidence: 99%
“…[11][12][13] By controlling treatment factors during the direct fluorination process, a surface layer containing C-F bonds with preferable surface properties can be obtained. 14,15 In An's research, by controlling direct fluorination time and temperature, different surface conductivities are obtained in epoxy resins. [16][17][18] The dc surface flashover voltage of the epoxy resin is also found improved after direct fluorination.…”
Section: -2mentioning
confidence: 99%
“…It needs to be pointed out that there is a small oscillating signal just after the laser target electrode signal in measured current traces, which was found to be pertinent to the length of the wire connecting the HV electrode to the power supply isolating capacitor (in Figure 1). Although we have tried to shorten the wire length so that the oscillating signal is compressed and becomes closer to the target electrode signal, in comparison with our previous published results [19], it still has a small contribution to the signals just after the laser target electrode signal, as shown by the arrow in Figure 4b in the following text.…”
Section: Space Charge Measurementsmentioning
confidence: 72%
“…However, when oxygen as impurity was present in the fluorinating gas mixture at a low concentration, a thick fluorinated layer or a long treatment time was needed to reduce the space charge densities by the same amount [19]. We also found that fluorination time needed for effective suppression of the space charge could be significantly reduced by increasing fluorination temperature, for instance, from 240 minutes at 55 °C [19] to 120 minutes at 70 °C [20].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The research works and applications are mainly concentrated on the improvements of the barrier properties, wettability, adhesiveness, chemical stability or biocompatibility of polymers [18,19] and dealing with the electrical properties of polymers. For example, An et al [20,21] indicated that surface fluorination of PE has a significant influence on the charge injection and accumulation. Du et al [22,23] found that surface fluorination is an effective method for modulating the electrical properties and restraining the surface charge and space charge accumulation of the PI film.…”
Section: Introductionmentioning
confidence: 99%